HAUSAT-2 Satellite Radiation Environment Analysis and Software Hamming Code EDAC Implementation - Ji-Wan Jung; Young-Keun Chang (Journal of Astronomy and Space Sciences, 2005)
This paper addresses the results of HAUSAT-2 radiation environment and effect analyses, including TID and SEE analyses. Trapped proton and electron, solar proton, galactic cosmic ray models were considered for HAUSAT-2 TID radiation environment analysis. TID was analyzed through total dose-depth curve and the radiation tolerance of TID for HAUSAT-2 components was verified by using DMBP method and sectoring analysis. HAUSAT-2 LET spectrum for heavy ion and proton were also analyzed for SEE investigation. SEE(SEU, SEL) analyses were accomplished for MPC860T2B microprocessor and K6X8008T2B memory. It was estimated that several SEUs may occur without SEL during the HAUSAT-2 mission life(2 years). Software Hamming Code EDAC has been implemented to detect and correct the SEU. In this study, all radiation analyses were conducted by using SPENVIS software.